Readiness for Change in the Hospitality Industry in Indonesia - Fiska Maya Saptari; Nidya Dudija (Journal of Economics, Business, and Accountancy Ventura, 2024)
This study aims to obtain empirical evidence regarding the influence of organizational culture, perceived organizational support, and organizational commitment on readiness for change. This type of quantitative research is quantitative research where the sample is 111 respondents who were analyzed using SEM-PLS. The results showed that organizational culture, perceived organizational support, and organizational commitment positively affect readiness for change. Studies show that if the organizational culture, perceived organizational support, and organizational commitment are reasonable, it will increase employee readiness for change during the COVID-19 pandemic in Indonesia. This research implies that The Royale Krakatau Hotel can create a web-based knowledge management system or application that can distribute employee knowledge anywhere and anytime. Second, it is important to pay attention to non-financial support, such as providing a more transparent employee of the month so that employees feel that the assessment is correct. Third, the organization can routinely look up to and calculate the workload of each employee so that the compensation and workload provided by the company are by the provisions without harming employees. Fourth, a change agent should be formed to manage any resistance to change and be more sensitive to the reasons why employees resist change to improve the employees' ability to understand and manage resistance to change.